Management of ginger bacterial wilt (Ralstonia solanacearum) epidemics by soil solarization and botanical mulching at Tepi, southwestern Ethiopia - Jibat, Merga; Getu, Abukiya (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
Ginger is one of the most valuable cash crops for farmers in different parts of Ethiopia. Bacterial wilt disease, caused by Ralstonia solanacearum, creates major limitation to production of ginger in Ethiopia. Heavy losses due to the disease occur regularly, causing an additional impediment for production in infected areas. Field tests were conducted at Tepi, South-Western Ethiopia, during the 2019 and 2020 main cropping seasons to assess the effectsof soil solarization and botanical mulch on epidemics of bacterial wilt of ginger. Four soil solarization periods, lasting two, four, six or eight weeks before planting were integrated with four different botanical mulch treatments after planting: vetivar grass, lemon grass, Chinese chive and Lantana camara. Unsolarized and unmulched plots were used as the control for comparison. Treatments were arranged in factorial arrangements with randomized complete block design with three replications. The outcomes indicated that soil solarization integrated with lemon grass mulch treatments significantly reduced bacterial wilt mean incidence by 22.1% up to 42.2%, compared to control plots. These treatments also dramatically reduced AUDPC and disease progress rates. Soil solarization for eight weeks integrated with lemon grass mulch resulted in the lowest (42.2%) final mean disease severity and AUDPC (33.8%) in comparison to the control. Typical results of this study indicated that soil solarization integrated with botanical mulch treatments were effective in slowing dawn the epidemics of bacterial wilt and in recovering ginger production and productivity, and they are consequently recommended for application in the study areas along with other crop management schemes.
Keywords: ginger; bacterial wilt; mulching; soil solarization; plant disease management